Perancangan Dog Furniture untuk Rumah Tinggal - Valentia Aquany Herlie Sutanto (Intra, 2017)
The interaction of humans and pets, especially dogs has become a very important need both inside and outside the room. To accommodate the interaction of the joint activity between human and dog within the main room of the living room, it is necessary to identify what activities can be performed together and the type of furniture required. How to design the necessary furniture and flexibility to be used in the living room, dining room, and bedroom is also a problem that has been solved.This design method was adopted from Sarah Gibbons, the first step is to observe the activities of human and dog in the family room, dining room, and bedroom. On the results of observations made, determined design limitations for designing dog furniture. In addition to observation of the activity, observations were also conducted on dog characters. The results of this observation will have an impact on the shape and material of dog furniture design.The result of designing dog furniture is to accommodate human activities with dogs. The types of furniture that are accommodated are the facilities of work areas, seating facilities, and storage facilities. Design of this dog furniture, each furniture item accommodates two needs of activity as well as flexible design to be moved in three rooms by recomposing based on the needs of each room.